Effect of wavelengths and excitation density on the optical properties of P3HT: SiNWs bulk heterojunction for photovoltaic applications. (September 2016) - Hidouri, T.; Saidi, H.; Amri, C.; Saidi, F.; Bouazizi, A.
Abstract: In this work, hybrid nano-composite based on poly (3-hexylthiophène) P3HT and silicon nanowires (SiNWs) were prepared by Ag-assisted chemical etching method (MACE) on n-type (100) Si substrate. We study the influence of the power and wavelength excitation on photoluminescence (PL) properties. We note that charge transfer between poly (3-hexylthiophène) and SiNWs is more pronounced using an excitation of 488 nm than 514 nm. This result correlates with the penetration depth found. Luminescence keys as function of excitation density proves an explication of the charge behavior in hybrid structure. A red shift of the PL peak was noted with increasing the excitation density for 488 nm and 514 nm excitation due to the confinement effect. Highlights: P3HT is deposited directly on Si substrate by spin-coating method. Optical properties of SiNWs and P3HT: SiNWs were investigated. SiNWs were prepared using metal assisted chemical etching. Variation of wavelengths and excitation density were investigated to study the optical properties.